PENGGUNAAN VIDEO ANIMASI UNTUK MENINGKATKAN PENGETAHUAN SEKSUALITAS ANAK USIA 5-6 TAHUN - Azizah Aini; Sofyan, Hendra; Utami, Winda Sherly (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
Animated videos are one of the means to optimize effective sexuality knowledge for kindergarten children. This study aims to determine the effect of using animated videos on the sexuality knowledge of children aged 5-6 years at TKIT Pelita Doktora. This type of research is quantitative research using experimental methods. The design used is pre-experimental design with a one group pretest-posttest design. The population in this study was 16 children at TKIT Pelita Doktora. The sampling technique used was total sampling. The instrument used was an observation sheet. The data analysis techniques used were normality test, homogeneity test and hypothesis test. The results of the study prove that the t count value, which is 31.833 t count> t table 2.131, then H0 is rejected and Ha is accepted. It is concluded that variable X has an effect on variable Y. With a strong interpretation with a value of 7.40 which is in the range> 1.00 with a strong interpretation (strong effect). Thus, the use of animated videos can be applied to improve children's sexuality knowledge.